Collaborative marketing for the sustainable development of community-based tourism enterprises: voices from the field. Issue 8 (3rd August 2018) - Ngo, Tramy; Lohmann, Gui; Hales, Rob
ABSTRACT: This paper examines stakeholder engagement in the collaborative marketing of community-based tourism enterprises (CBTEs). The study explored the various collaborative marketing approaches shaped by diverse stakeholders' perspectives on ways to achieve the sustainable development of CBTEs in Vietnam. The results of 30 in-depth, semi-structured interviews from three CBTEs in Vietnam showed that three collaborative marketing approaches were prevailed among CBTE stakeholders and were categorised as commercial viability-driven, community development-driven and balanced approaches. The approaches' differences were reflected in the marketing objectives to achieve CBTE sustainability, the central linkages of CBTE collaborative marketing, and the facilitators of stakeholder collaboration. The research found a knowledge gap between researchers and research participants and divergent perspectives among different categories of research participants regarding marketing and CBTE sustainability. This paper implies the role of a knowledge co-production approach to drive the stakeholder engagement in CBTE collaborative marketing for CBTEs' long-term success. Additionally, this study provides insights into the discussion of marketing for sustainable tourism. Furthermore, the findings contribute to a better understanding of the collaborative approach at the organisational level.